Insect pest control in agriculture. Changing scale: from field to landscape - Goebel, François-Régis (Perspective, 2013)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Over the last 20 years, insect pest pressure on agriculture has been increasing. This growing pressure is explained by the expansion of monocropping and the intensification of farming practices, which are altering landscapes and reducing biodiversity. It is reinforced by climate change, which causes tropical insects to migrate to temperate zones and modifies insect biology. Controlling this growing pressure while reducing or ending pesticide application implies no longer acting solely at field level, but also at landscape level. This scale change makes it possible to use biodiversity to regulate pests, and also to coordinate stakeholder practices, as shown by attempts to control sugarcane and cotton plant pests. However, it requires detailed knowledge of the interactions between pest populations and their natural enemies, and also between landscape components, biodiversity and human activities, which opens up new avenues for transdisciplinary research."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value="{"1":2,"2":"Over the last 20 years, insect pest pressure on agriculture has been increasing. This growing pressure is explained by the expansion of monocropping and the intensification of farming practices, which are altering landscapes and reducing biodiversity. It is reinforced by climate change, which causes tropical insects to migrate to temperate zones and modifies insect biology. Controlling this growing pressure while reducing or ending pesticide application implies no longer acting solely at field level, but also at landscape level. This scale change makes it possible to use biodiversity to regulate pests, and also to coordinate stakeholder practices, as shown by attempts to control sugarcane and cotton plant pests. However, it requires detailed knowledge of the interactions between pest populations and their natural enemies, and also between landscape components, biodiversity and human activities, which opens up new avenues for transdisciplinary research."}" data-sheets-userformat="{"2":585,"3":[null,0],"6":{"1":[{"1":2,"2":0,"5":[null,2,0]},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"12":0}">Over the last 20 years, insect pest pressure on agriculture has been increasing. This growing pressure is explained by the expansion of monocropping and the intensification of farming practices, which are altering landscapes and reducing biodiversity. It is reinforced by climate change, which causes tropical insects to migrate to temperate zones and modifies insect biology. Controlling this growing pressure while reducing or ending pesticide application implies no longer acting solely at field level, but also at landscape level. This scale change makes it possible to use biodiversity to regulate pests, and also to coordinate stakeholder practices, as shown by attempts to control sugarcane and cotton plant pests. However, it requires detailed knowledge of the interactions between pest populations and their natural enemies, and also between landscape components, biodiversity and human activities, which opens up new avenues for transdisciplinary research.